2021
DOI: 10.21037/apm-21-122
|View full text |Cite
|
Sign up to set email alerts
|

The expression levels of plasma dimethylglycine (DMG), human maternally expressed gene 3 (MEG3), and Apelin-12 in patients with acute myocardial infarction and their clinical significance

Abstract: Background:To analyze the expression levels of plasma dimethylglycine (DMG), human maternally expressed gene 3 (MEG3), and Apelin-12 in patients with acute myocardial infarction (AMI) and explore their clinical significance.Methods: One hundred and ten patients with suspected AMI (chest pain duration <6 h) who were admitted to our hospital between December 2018 and June 2020 were included. Plasma DMG, MEG3, and Apelin-12 levels were measured at the time of admission. The levels of plasma DMG, MEG3, and Apelin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…The correlation between lncR-Meg3 and acute myocardial infarction was confirmed (Wei and Wang, 2021). The researchers measured the serum concentrations of dimethylglycine (DMG), Apelin-12, and lncR-Meg3 in 110 patients with acute chest pain for more than 6 h, Results showed that the levels of lncR-Meg3 in acute myocardial infarction (AMI) groups were approximately two times higher than those in healthy individuals.…”
Section: Lncr-meg3 and Diagnosismentioning
confidence: 86%
“…The correlation between lncR-Meg3 and acute myocardial infarction was confirmed (Wei and Wang, 2021). The researchers measured the serum concentrations of dimethylglycine (DMG), Apelin-12, and lncR-Meg3 in 110 patients with acute chest pain for more than 6 h, Results showed that the levels of lncR-Meg3 in acute myocardial infarction (AMI) groups were approximately two times higher than those in healthy individuals.…”
Section: Lncr-meg3 and Diagnosismentioning
confidence: 86%
“…Apelin-12, one of the most potent active forms of apelin, has been widely studied in the cardiovascular system. It has been reported that the plasma concentration of apelin-12 after acute myocardial infarction (AMI) is significantly lower than that in the control population [ 15 , 16 ]. Apelin-12 is negatively associated with troponin I levels, high-sensitivity C-reactive protein, neutrophil/lymphocyte ratio, and the rate of MACE, indicating that apelin-12 can serve as a prognostic biomarker for STEMI patients [ 9 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study showed that there was no correlation between apelin-12 and the degree of coronary artery stenosis indicated by the Gensini score. However, a study by Topuz suggested that apelin-12 was negatively correlated with the angiographic severity, as assessed according to the SYNTAX score [ 16 ]. This discrepancy may be due to the different sample sizes and methods used to assess the degree of coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were any of the following: (1) type 1 diabetes, or diabetes induced by drugs or other endocrine disorders. (2) active infection or fever within two weeks before admission; (3) self-reported severe alcohol abuse; (4) autoimmune diseases, including rheumatoid arthritis, systemic lupus erythematosus, anaphylactoid purpura; (5) neuropathy or psychiatric diseases, such as multisystem atrophy, epilepsy, depression; (6) severe organ diseases; (7) tumors; (8) patients with incomplete clinical information or laboratory results.…”
Section: Participants and Study Designmentioning
confidence: 99%
“…Apelin-12 is one of the pharmacologically active apelin isoforms involved in various diseases such as intracranial atherosclerotic diseases [5], diabetes [6] and acute myocardial infarction [7]. Previous studies have demonstrated that serum apelin-12 was related to metabolic disorders.…”
Section: Introductionmentioning
confidence: 99%